The Educational Value Of Emotional Intelligence For Choreographic Education - Talpă, Svetlana (Didactica Danubiensis, 2025)
development of choreography students and to demonstrate its relevance in choreographic education, as reflected in the university curriculum in choreographic art, which emphasizes the development of students’ emotional skills. The study further examines how these skills influence artistic performance, stage communication, and the psycho-emotional balance of dancers. Previous studies examine the interdependence between emotional intelligence and educational processes in the arts, with particular attention to emotional self-regulation, emotion management, empathy, and motivation, which are fundamental concepts in choreographic education. These studies provide support for the integration of emotional skills into the arts education curriculum. Approach: The study is grounded in the scientific substantiation of research findings, outlining key approaches to emotional intelligence in choreographic education through qualitative methods, including observation and case studies within choreographic education contexts. Research results: The study identifies psychobehavioral traits that influence the development of reflexive and expressive skills in the arts. The cultivation of emotional intelligence supports students’ adaptation during stage performances and enhances interpersonal relationships within the artistic ensemble. Implications: This study offers strategic guidance for teachers, researchers, and educational decision-makers to optimize artistic training programs. It emphasizes the development of emotional intelligence in choreographic education and provides recommendations for fostering these skills, which are relevant to dance teachers and the success of dance teacher training in higher education. The study also examines how arts programs contribute to the development of emotional intelligence by promoting self-awareness, empathy, and interpersonal skills. Furthermore, choreographic education strategies are explored as methods that support the development of emotional intelligence through dance. The value of this research lies in its innovative approach to integrating emotional intelligence into choreographic education, providing an interdisciplinary perspective that highlights the development of emotional competencies essential for the personal and professional success of dancers.